(untitled) (MAUSAM, 1976)
The crustal structure of the eastern Himalayas, adjoining Tibetan Plateau and Chinese mountains has been investigated from body wave data of near earthquakes. A three layered crustal model consisting of two granitic layers (granite I and II) and one basaltic layer has been interpreted. Wave velocities for Pg1, Pg2, P and Pn phases have been observed to be as 5.65, 6.03, 6.49 and 7.97 km/sec and for Sgl’, Sg2’ S, tunnel to than Sn phases to be as 3.42, 3.60,3.90 and 4.53 km/sec respectively. It has also been observed that the wave velocity increases with depth in the granite I layer. The average thickness of the crustal layers for granite I are found to be as 22.0 km, for granite II as 12.3 km and for basaltic layer as 16.1 km. The average depth of the, M-discontinuity in the region has been interpreted as 504 km. It has also been observed that the crust-mantle boundary dips at an angle of about 30’ from south to north along Long. 103°E. A general thickening of the crust has also been observed in the eastern Himalayas from Kunming towards Lhasa.